Bisbenzylisoquinoline alkaloids inhibit influenza virus replication by disrupting endosomal acidification - Bo Li; Lijun Qiao; Xingqiong Li; Ge Yang; Kun Wang; Huiqiang Wang; Shuo Wu; Haiyan Yan; Jiandong Jiang; Yuhuan Li (Virology Journal)
Abstract Influenza virus, known for causing recurrent epidemics and pandemics, pose a significant public health challenge due to their rapid mutation rates and the emergence of drug resistance. This emphasizes the urgent need for the development of novel antiviral drugs. In this study, we identified five bisbenzylisoquinoline alkaloids (BBAs)—cepharanthine (CEP), tetrandrine (TET), fangchinoline (FCN), berbamine (BBM) and iso-tetrandrine (Iso-TET)—that exhibit antiviral activity against influenza virus, as determined through cytopathic effect inhibition screening. These compounds showed dose-dependent suppression of viral replication by targeting the early stages of the viral life cycle, specifically through disruption of endosomal acidification and inhibition of viral genome release into the cytoplasm. Notably, treatment with the representative compound CEP significantly reduced viral load in the lungs and improved lung pathology in infected models. These findings highlight the potential of BBAs, particularly CEP, as promising candidates for the development of therapeutics against influenza virus infections.